The Gesangleiter in Joseph Riepel’s Baßschlüssel (1786) – First Part - Stefan Eckert (Zeitschrift der Gesellschaft für Musiktheorie, 2014)
Joseph Riepel’s Anfangsgründe zur musikalischen Setzkunst (Fundamentals of Musical Composition) is an important source for our understanding of eighteenth-century compositional theory and pedagogy. One of the most noticeable aspects of the Anfangsgründe is the fact that the treatise is written in dialogue form. Only the chapter published posthumously in 1786, the Baßschlüssel (Bass clef), which focuses on how to write a bass against an existing melody, does not, except for the last four pages, follow the dialogue format. Because of this, the Baßschlüssel seems to present a different theoretical approach to composition. Most noteworthy is the absence of other theoretical positions that result from the typical back and forth between teacher and student. While the original manuscript upon which the edited version is based does not seem to have survived, a manuscript copy held in the British Library (GB-Lbl Add. 31034) contains at least twelve pages in dialogue form that are related to the Baßschlüssel, but that are not part of the published chapter. These twelve pages relate to Riepel’s Gesangleiter, his instruction on how to harmonize ascending and descending scale steps in the upper voice, which follows his discussion of the Baßleiter, the harmonization of scale steps in the lowest voice, or bass. The following essay, provides an overview of the Gesangleiter in Riepel’s Baßschlüssel, followed by a discussion of the manuscript pages as compared to the published version and a transcription of the manuscript pages.